Розкопки багатошарового поселення в Ужгороді-Горянах - Котигорошко, В.Г.; Мойжес, В.В.; Щербей, К.І. (Археологічні дослідження в Україні, 2010)
During the 2009 season the excavations of multilayer settlement in Uzhhorod-Horyany were ongoing that allowed the authors to specify the main stages of settling the Rotonda tract: the first is the Neolithic Age, the second — the Hallstatt period, the third — the Late Roman times, the fourth and the fifth — the Mediaeval period (from the end of the 11th c. to the 12th c. and from the 15th c. to the 16th c.).